Peer’s pressure effects : secondary school student’s dropout behaviour and young offenders - Menegaa Paraman,; Rosila Bee Mohd Hussain, (Penerbit Universiti Kebangsaan Malaysia, 2022)
This study aims to identify the peer’s pressure effects on students especially among secondary school students who tend to lose focus in teaching and learning process in school and facing individual identity challenges, behaviour and disciplinary issues. This qualitative study was conducted by interviewing a total of 40 Indian dropout students from secondary schools who were selected as the study sample in Selangor State. Based on the results, it was found, student’s attitudes that very close to their peers without their parent’s knowledge in school and out of school environment and its negative effects influencing students to lose focus in teaching and learning process. Building on detailed information on negative influences through friendship networks, this study found evidences, peer’s pressure factor influencing students to left behind in their academics followed by a significant reduction in grade repetition and eventually lead them to dropout from school and involve in other social issues. Student’s involvement in school dropout issues and then in criminal activities as young offenders questioning their social bonds to the school system and social environmental effectiveness in increasing youth’s delinquency in society. Finally, the study implications were discussed and some appropriate recommendations were highlighted to reduce student’s negative influences through peer’s factor while improving teaching and learning style effectiveness in schools environment. Additionally, the study results can help the school management to inculcate good values and awareness among young teenagers to stay away from social issues or other crimes, so that they will become progressive individuals for their future well-being.